Efektivitas layanan bimbingan kelompok dengan menggunakan teknik problem solving untuk meningkatkan interaksi sosial siswa pengguna smartphone - Nasrul, Febriyeni; Suhaili, Neviyarni (JPGI (Jurnal Penelitian Guru Indonesia), 2022)
Social interaction of smartphone users is growing among teenagers today, causing various kinds of changes in attitudes and behavior of teenagers, including preferring to be alone with their smartphone. Teenagers prefer to communicate with friends who are in a smartphone user community rather than interacting with friends in their environment. The purpose of this study is to find out (1) to analyze the differences in the social interactions of students using smartphones in the experimental group before and after being given treatment with group guidance services with problem solving techniques, (2) to analyze the differences in the social interactions of students using smartphones in the control group before and after being given the treatment of guidance services. group without using problem solving techniques (regular group guidance), (3) Analyzing differences in the social interactions of students using smartphones in the experimental group after being given treatment with group guidance services with problem solving techniques, with control group students being treated with group guidance services without using problem solving techniques.The research method used is quantitative research, this type of research is quasi-experimental. The sample of this study was 9 students for the experimental group and 10 students for the control group. Sampling was done by non-random sampling and purposive sampling. The research instrument used a Likert scale model, the data were analyzed using the Wilcoxon signed ranks test and the Kolmogorov Smirnov 2 independent samples with the help of SPSS version 20.00.The results showed that (1) there were significant differences in the social interactions of students using smartphones in the experimental group before and after being given treatment with group guidance services with problem solving techniques, (2) there were significant differences in the social interactions of students using smartphones in the control group before and after being given treatment. group guidance services without using problem solving techniques (ordinary group guidance), (3) there are differences in the social interaction of students using smartphone in the experimental group after being given treatment with group guidance services with problem solving techniques, with control group students being treated with group guidance services without using problem techniques. solving, this can be seen in the posttest average score of the experimental group rose higher than the posttest average score of the control group. Thus, group guidance services with problem solving techniques are effective in increasing the social interaction of smartphone users.